ANALISIS MODEL ANTREAN NON POISSON DAN UKURAN KINERJA SISTEM PELAYANAN MENGGUNAKAN GUI R - Luthfi Nashukha Dewi; Sugito Sugito; Alan Prahutama; Mustafid Mustafid; Dwi Ispriyanti Dwi Ispriyanti (Jurnal Statistika Universitas Muhammadiyah Semarang, 2021)
The queue process is a process related to the arrival of a customer at a service facility, then waits in line if not yet received service and leaves the service facility after receiving service. The queue occurs because many people need services at the same time and the number of service facilities available is limited. In this case, the arrival pattern follows the Poisson distribution assuming the arrival is random. Departement of Population and Civil Registration in Semarang City (Dispendukcapil) is one of the public service places that often arise in line. Therefore, this system needs to be applied with queue theory. The queue theory was developed to provide a model in determining system performance. The queue model that has been obtained at every counter in  Dispendukcapil is customer service (UNIF/LOGN/1):(GD/∞/∞), legalized (UNIF/LOGN/2):(GD/∞/∞), data changes (UNIF/BETA/1):(GD/∞/∞), birth (UNIF/BETA/2):(GD/∞/∞), death (UNIF/BETA/2):(GD/∞/∞), second quote (UNIF/LOGN/1):(GD/∞/∞), biometric (UNIF/LOGN/2):(GD/∞/∞), resident registration (UNIF/LOGN/2):(GD/∞/∞), electronic ID Card recording (UNIF/GAMM/1):(GD/∞/∞). In measuring the performance of the system obtained through the GUI R. Based on the results obtained, the Dispendukcapil service system is optimal because of the low waiting time.